AKIBAT HUKUM PERKAWINAN TIDAK DICATAT TERHADAP ISTRI DAN ANAK ATAS HAK KEBENDAAN MENURUT HUKUM ISLAM DI INDONESIA - Siah Khosyi’ah (Asy-Syari'ah, 2016)
This paper describes the legal consequences of marriage were not recorded on the wives and children of the right material according to Islamic law in Indonesia, so this article is focused on the history of marriage in Indonesia, marriage is not recorded, and the legal consequences of marriage were not recorded for the right material. Legal remedies that can be done to make the recognition of the state for the marriage were not recorded, namely through the filing legalitation of marriage (isbat nikah) to the Islamic Courts. In Islamic Law Compilation explained that: who has the right to apply for legalitation of marriage (isbat nikah) is a husband or wife, their children, the guardian of marriage, and interested parties.